History Subject Teaching and Learning Strategies of the 2013th Curriculum in SMA Negeri 48 Jakarta - Pangestu, Ghalih Purwo; Wisnubroto, Wisnubroto; Husmiati, Ratu (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to determine history learning strategies at SMA Negeri 48 Jakarta. This research used qualitative methods. Data collection techniques in this research were observation, interviews and documentation. The data sources used in this research consisted of core informants that include the history subject teacher and class X IPS 1 students, totaling 36 students. The results of this research show that teachers use different learning strategies. History subject teachers are more synonymous with providing historical understanding through discussions, assignments, mind mapping, emphasizing students' individual ability to speak in public, and a responsible attitude, as well as historical understanding through lectures, questions and answers, group assignments using power point media and emphasizing abilities. individual or group to be able to speak in public and a sense of responsibility.